2016
DOI: 10.1039/c6tc03157a
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric pressure sensors based on cyano-substituted oligo(p-phenylene vinylene) derivatives in the hybridized local and charge-transfer excited state

Abstract: D–A type dye exhibits high emission efficiency and ratiometric piezochromism behavior due to HLCT characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Remarkably, the magnitude of the PL spectral shift for the TPEB‐α crystals upon increasing hydrostatic pressure (Δλ em,max = 212 nm) is unprecedented (Figure ). To elucidate the large redshift, we prepared the HLCT‐active luminophor mF‐TPA, which has PLQYs as high as 82.6% 8. However, the pressure‐induced redshift in mF‐TPA (Δλ em,max = 146 nm) was far smaller than that of TPEB‐α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the magnitude of the PL spectral shift for the TPEB‐α crystals upon increasing hydrostatic pressure (Δλ em,max = 212 nm) is unprecedented (Figure ). To elucidate the large redshift, we prepared the HLCT‐active luminophor mF‐TPA, which has PLQYs as high as 82.6% 8. However, the pressure‐induced redshift in mF‐TPA (Δλ em,max = 146 nm) was far smaller than that of TPEB‐α.…”
Section: Resultsmentioning
confidence: 99%
“…This combination is a “win‐win” tactic: the former contributes to high PLQYs, while the latter guarantees high sensitivity to external stimuli. Accordingly, HLCT‐type cyano‐substituted oligo(p‐phenylene vinylene) (CN‐OPV) demonstrated a clear bathochromic shift (Δλ max > 145 nm) in its PL color from the visible to the near‐IR region (λ max = 765 nm) upon exposure to high pressure . Clearly, D–π–A‐type luminophors with high brightness have great potential to show the clear color differences and strong penetrability characteristic.…”
Section: Introductionmentioning
confidence: 83%
“…The field of intermolecular CT crystals or salts mostly focused on high conductivity, superconductivity, or organic ferroelectrics properties,, and luminescence mechanochromism is still rare. To the best of our knowledge, the novelty of this work can be found in the following two points: a) High pressure study of luminescent co‐crystal with intermolecular CT interaction has not been reported, although the high pressure fluorescence study or intramolecular CT system has been reported ,,. b) An example of high‐pressure single‐crystal X‐ray diffraction analysis of piezochromic materials is still rare, although it has been performed for mono‐component crystal showing an excimer emission …”
Section: Figurementioning
confidence: 99%
“…As the applied pressure increased, the fluorescence emission of the 1 ⋅ guest clearly showed a gradual red shift, and the luminescence intensity gradually decreased (Figure a–c), which coincided with the previous results ,, For example, 1 ⋅ 4‐fluorotoluene showed a noticeable luminescence color change of over 100 nm from cyan (483 nm at 0.2 GPa) to red (593 nm at 8.7 GPa) under UV light excitation as shown in Figure a, which is more significant than upon mechanical grinding. Moreover, luminescence recovery from red to cyan was achieved under a decompression process.…”
Section: Figurementioning
confidence: 99%
“…In addition, a clear decreasing trend of the h PL in the different solvents is observed, which is ascribed to the CT effect depending on solvent polarity. 19,20 To evaluate the solvatochromic effect, the Lippert-Mataga model is applied to estimate the dipole moment (m e ) of the excited state. The plot of Stokes shi against orientation polarizability (Df) is shown in Fig.…”
Section: Solvatochromic Effectmentioning
confidence: 99%